The Main Approaches to Economic Diagnostics of the Power Engineering Enterprises - T. F. Mantserova; D. A. Lapchenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The features of economic diagnostics of power engineering enterprises in the Republic of Belarus are considered. Accounting and analysis of the activities of enterprises of the power system in the emerging energy market requires improving approaches of economic monitoring. This can be achieved through a comprehensive system of economic diagnostics of the enterprise. The structure of economic diagnostics is represented by three elements, viz.: rapid diagnostics, diagnostics of bankruptcy and complex diagnostics of the economic condition, each of which has its own purpose and objectives of the study, as well as its own content of the reports to be analyzed reporting and of analytical procedures to be fulfilled. The choice of methods of economic diagnostics also depends on the stage of the life cycle of the enterprise. But it is the specificity of the type of economic activity that has a major impact on the diagnosis. The article describes the specific features of using methods of express-diagnostics, diagnostics of bankruptcy based on multivariate models as well as of integrated diagnosis of power utilities (by example of “Oblenergo” enterprises). The study demonstrated that the use of universal financial ratios in rapid assessment and models for assessing the risk of bankruptcy for domestic energy enterprises is not quite suitable, since these methods do not take into account the existing specifics of the structure of the capital of the organizations of power engineering system. The authors came to the conclusion that each of the approaches to diagnosis makes it possible to evaluate only individual criteria of the state of the economy of the organization. To improve the efficiency of analytical work at the enterprises of the power system, it is necessary to improve diagnostic procedures taking into account the technological features of production and the influence of factors of the external and internal environment. Only a comprehensive diagnosis can give a comprehensive unbiased assessment of the enterprise at all stages of its life cycle.